Sugar market policies in the EU and international sugar trade - Jurij Berger; Bernhard Brümmer; Dela-Dem Fiankor; Thomas Kopp (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2021)
In the EU, the 2017/18 sugar marketing year (MY) was the first with no production quota and most of the price support gone. The Uruguay round restrictions on sugar exports were also not binding anymore, making the EU a net exporter. In MY2018/19 the EU turned back into a net importer as domestic sugar production fell. Developments on the demand side have been much less dramatic as global sugar consumption kept growing. These market and policy trends lead to relatively low international prices between 2018 and 2020 before trending upwards in 2021. These low prices were at least partially transmitted to European markets. In a net-export situation and without export restitutions, international export prices would be the anchor for intra-EU price formation. Under these circumstances, the still present interventionist side of the EU's sugar market policy could easily be viewed as irrelevant for price formation within the EU. However, in the more realistic scenario of the EU being a net-importer, price formation will continue to be strongly affected by the existing import restricting policies. There has been no change in the EU schedule of bound tariffs for sugar since the formation of the World Trade Organisation. Other external sugar market policies of the EU are unilateral market access to the common market (i.e., EPA, EBA), tariff rate quotas (e.g., the Balkan and CXL preferences) and preferences granted under bilateral agreements. This report assesses how effective the EU trade policies regarding sugar have been for EU sugar imports and sugar prices within the EU, followed by resulting policy recommendations. [...]
Additional information: A study commissioned and partially funded by CIUS - The Association of European Sugar Users (cius.org).
Keywords: 330; Zuckermarkt; Zuckerpolitik; EU-Agrarpolitik; EU-Staaten; Wirkungsanalyse; Zucker; Preis; Welt